Anterior segment parameters associated with extramuscular manifestations in polymyositis and dermatomyositis - Zoltan Griger; Katalin Danko; Gabor Nemeth; Ziad Hassan; Zsuzsa Aszalos; Katalin Szabo; Levente Bodoki; Rudolf Gesztelyi; Judit Zsuga; Peter Szodoray; Adam Kemeny-Beke (International Journal of Ophthalmology, 2020)
AIM: To evaluate detailed anterior segment parameters of patients with idiopathic inflammatory myopathies (IIM), including polymyositis (PM), and dermatomyositis (DM), and to clarify the associations between these data and clinical variables of IIM. METHODS: Totally 57 PM, 41 DM patients and 62 controls were enrolled in this cross-sectional, observational, case-control study. All study participants underwent Pentacam evaluation. Laboratory investigations consisted of different antibody assays, while extramuscular clinical assessments included Raynaud’s phenomenon, dysphagia, interstitial lung disease, arthritis/arthralgia, and weight loss. Objective signs and subjective symptoms of dry eye disease (DED) were also evaluated. RESULTS: All pachymetric parameters [center, apex, thinnest and maximal keratometry (Kmax)] and corneal volume (CV) of both sides of PM patients proved to be significantly lower. Some pachymetric data were also noticed as significantly decreased compared to those of controls. Several significant differences were traced between anterior segment values and extramuscular manifestations of myositis, largely in case of arthritis/arthralgia and weight loss, whereas associations between anterior segment parameters and antibodies were weak. Objective clinical tests of DED were also significantly decreased in IIM patients. CONCLUSION: The results suggest that all IIM patients have thinner corneas compared with those of controls, and decreased corneal parameters are significantly associated with the occurrence of some extramuscular manifestations. In addition, IIM patients tend to develop objective signs of DED.